Initial combination of linagliptin and metformin in patients with type 2 diabetes: efficacy and safety in a randomised, double-blind 1-year extension study - Haak, T (Int J Clin Pract, 2013)
OBJECTIVE: To determine the efficacy and safety of linagliptin in initial combination with metformin in patients with type 2 diabetes. METHODS: This 1-year randomised, double-blind study was an extension of a 6-month randomised controlled trial, in which adults with type 2 diabetes received one of six treatment regimens (linagliptin 2.5 mg plus metformin 500 mg bid, linagliptin 2.5 mg plus metformin mg 1000 bid, metformin 1000 mg bid, metformin 500 mg bid, linagliptin 5 mg qd or placebo). In the extension, patients in the first three treatment groups continued their regimen (non-switched group, n = 333) while the metformin 500 mg bid, linagliptin 5 mg qd and placebo groups were re-randomised to one of the three continuing regimens (switched group, n = 233). RESULTS: All three non-switched groups maintained reductions in glycosylated haemoglobin (HbA1c; mean ± standard deviation reductions across the 1.5-year period: linagliptin 2.5 plus metformin 1000 bid, –1.63 ± 1.05%; linagliptin 2.5 plus metformin 500 bid, –1.32 ± 1.06%; metformin 1000 bid, –1.25 ± 0.91%) while the switched groups showed additional HbA1c reductions. During the extension, there were no clinically meaningful changes in body weight in any group. Adverse event rates were similar between groups, with most events being mild or moderate, and the incidence of investigator-defined hypoglycaemia was low, with no severe events. DISCUSSION: Initial combination of linagliptin and metformin was well tolerated over the 1-year extension period, with low risk of hypoglycaemia, and improved glycaemic control vs. metformin alone. CONCLUSION: The initial combination of linagliptin and metformin appears to provide a useful treatment option in patients whose blood glucose levels are increased to an extent that metformin monotherapy may not achieve treatment targets.